Maternal Risk Factors Related with Term Low Birth Weight - Hina Shafi, Umber Asad, Rabia Nafees, Nazia Mushtaq, Shazia Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Low birth weight (LBA) remains to be an important community health issue globally. There are many fetal and maternal factors that contribute to low birth weight. The risk factors of maternal side are socially and biologically related. Low birth weight mortality can be condensed if risk factors from maternal side are perceived primarily and treated through simple procedures. Aim: This research was held to investigate maternal risk factors related with low birth weight. Study Design: A record-based retrospective and case control study. Place and Duration: In the Obstetrics and Gynecology department of Lahore General Hospital for six-months duration from 21st June 2021 to 20th December 2021. Methods: A retrospective, document-based, case-control study was conducted. The collection of retrospective data was performed on the basis of medical records from the department of the Obstetrics and Gynecology. Afterwards the criteria of exclusion and reviewing the integrity of the records, 80 subjects in patients’ group and 80 in control group were included with gestation age of more than 37-weeks. In Microsoft Excel; the data was entered and SPSS 23.0 was applied for data analysis. The chi-square test, student's t-test and odds ratio were applied to identify associated factors result in low birth weight. Results: 80 cases and 80 control groups were examined in this study. The mothers mean age in the study group was 25.1 ± 5.2 years and 23.1 ± 4.28 years in the control group. The patients mean weight was 61.8±6.91 kg in the patient’s group and 64.48±8.60 kg in the control group. The pregnancy-related diseases were noted 37.5% in the patient’s group and 32.5% in the controls group. Conclusion: Maternal factors such as socioeconomic status, haemoglobin, weight, and number of deliveries were related significantly with LBW. Maternal ailments, such as high blood pressure and diabetes, can result in a low birth weight. Keywords: Low birth weight, Maternal factors.